(untitled) (International Journal of Engineering and Computer Science, 2020)
Blockchain is defined as a group of unsegregated blocks over a P2P network. It is also considered as a decentralised ledger which holds the records of any online event. It offers a secure platform for knowledge and value transfer even in an untrustworthy network. In digital transactions on blockchain, each transaction is verified by all the nodes within the network using consensus protocol. Through this paper we will give a comprehensive overview of how Blockchain technology works, its current and future applications and how it can change the digital events in future.